21st AIAA Aerodynamic Decelerator Systems Technology Conference and Seminar 2011
DOI: 10.2514/6.2011-2524
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Inflatable Aerodynamic Decelerator (HIAD)Technology Development Overview

Abstract: The successful flight of the Inflatable Reentry Vehicle Experiment (IRVE)-3 has further demonstrated the potential value of Hypersonic Inflatable Aerodynamic Decelerator (HIAD) technology. This technology development effort is funded by NASA's Space Technology Mission Directorate (STMD) Game Changing Development Program (GCDP). This paper provides an overview of a multi-year HIAD technology development effort, detailing the projects completed to date and the additional testing planned for the future.The effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 1 publication
0
29
0
Order By: Relevance
“…In general, the use of a deployable aeroshell allows the vehicle to be decelerated at a higher altitude compared with a conventional rigid reentry vehicle. This provides several advantages for the entry, descent, and landing (EDL) approach, such as a lower heat load from aerodynamic heating and reduction in radio-frequency blackout [1][2][3][4][5][6][7][8][9]. Recently, a reentry vehicle with an inflatable aeroshell has also been developed in the Membrane Aeroshell for Atmospheric-entry Capsule (MAAC) project, in cooperation with several universities and JAXA.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the use of a deployable aeroshell allows the vehicle to be decelerated at a higher altitude compared with a conventional rigid reentry vehicle. This provides several advantages for the entry, descent, and landing (EDL) approach, such as a lower heat load from aerodynamic heating and reduction in radio-frequency blackout [1][2][3][4][5][6][7][8][9]. Recently, a reentry vehicle with an inflatable aeroshell has also been developed in the Membrane Aeroshell for Atmospheric-entry Capsule (MAAC) project, in cooperation with several universities and JAXA.…”
Section: Introductionmentioning
confidence: 99%
“…This technology can provide several advantages, e.g., reduction in aerodynamic heating during atmospheric reentry [1][2][3][4][5][6][7][8][9]. For flare-type thin-membrane aeroshells, several studies of elemental technologies and demonstration flights have been performed as part of the Membrane Aeroshell for Atmospheric-entry Capsule (MAAC) project [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The successful Inflatable Reentry Vehicle Experiment -II (IRVE-II) was completed on August 17, 2009 [7]. This experiment demonstrated that inflatable heat shields could maintain stability from hypersonic through subsonic speeds, which is a significant milestone to overcome for any EDL system.…”
Section: Current Iad Developmentmentioning
confidence: 95%
“…IRVE-II's success has generated considerable interest in the development of HIAD technology for atmospheric entry. In June 2010, the NASA Office of the Chief Technologist (OCT) initiated the HIAD Project to accelerate the development of HIAD technology [7].…”
Section: Current Iad Developmentmentioning
confidence: 99%
See 1 more Smart Citation